Digital Narcissism and Flying Monkey Behavior in Influencer Culture: A Structural Model of Toxic Loyalty among Online Consumer Communities: English - Wayan Sri Maitri; Komang Widhya Sedana Putra P; Ni Wayan Lasmi; Agus Purusa Dharma (University of Muhammadiyah Malang, 2026)
In today's digital era, influencer-marketing pervades consumers' perceptions and behavior—particularly in destinations such as Bali, where consumer culture online is intensifying with growing local digital subcultures. Follower tribes are frequently rife with toxic loyalty, where followers aggressively rush to the defense of influencers or brands even when there are obvious cases of ethics breaches or product failure. The current study examines the role of digital narcissism and the impact of flying monkey behavior—supporters who echo manipulative messages and suppress criticism—on irrational consumer loyalty. Despite increased emphasis on influencer power, there is sparse literature structurally capturing how narcissistic manipulation, mediated through flying monkey behavior, affects consumer behavior. This study bridges the gap by building a prediction model through Partial Least Squares Structural Equation Modeling (PLS-SEM). The data were collected from 200 social media users in Bali between 18 and 35 years old who were actively following domestic or national influencers. Measurement instruments were adapted from the Dark Triad Scale, relational aggression theory, and consumer susceptibility models. The findings indicate that digital narcissism highly predicts flying monkey behavior and irrational consumer loyalty, with flying monkey behavior partially mediating. The findings reveal the poisonous social dynamics that are codified within digital marketing ecosystems. Theoretically, this research bridges narcissistic communication theory and consumerism through a novel framework for exploring persuasive processes in online subcultures. In practice, it emphasizes the critically important need for ethical regulation of influencer communication and online community management. Following studies could assume longitudinal designs, investigate platform-based differences, or enlist biometric tools such as eye-tracking or sentiment analysis to expose deeper psychographic patterns. The present study also confirms the usefulness of subjecting the effects of digital communication power structures on loyalty, identity, and consumption in emerging digital society to critical examination.